Answer: One quarter of the force
Explanation:
According to Newton's law of Gravitation, the force
exerted between two bodies of masses
and
and separated by a distance
is equal to the product of their masses and inversely proportional to the square of the distance:
(1)
Where
is the gravitational constant
This means that the gravity force decreases when the distance between these two bodies increases.
In this context, if the distance between the capsule and the Earth increases twice, the new distance will be
.
Substituting this distance in (1):
(2)
<u>Finally:</u>
>>>This means the force toward Earth becomes one quarter "weaker"
Answer:
Surface tension is the tendency of liquid surfaces to shrink into the minimum surface area possible.
Surface tension is caused by effects of intermolecular forces at liquid interface.
Surface tension increases as intermolecular forces increases.
Explanation:
- Surface tension is the tendency of liquid surfaces to shrink into the minimum surface area possible. It can also be seen as the energy required to increase the surface of a liquid by a unit amount.
- Surface tension is caused by the mediating effects of intermolecular forces at the liquid interfaces. Example in water, surface tension is caused by the mediating effect of the force between hydrogen and oxygen molecules. Liquids tends to reduce their surface area because of inward attarction of the liquid molecules.
- Surface tension increases as intermolecular forces increases. Also, surface tension decreases as intermolecular forces decreases.
Answer:
6.22 N/m
Explanation:
From Hooke's law we deduce that F=kx where F is the applied force and k is the spring constant while x is the extension or compression of the spring. Making k the subject of the above formula then
![k=\frac {F}{x}](https://tex.z-dn.net/?f=k%3D%5Cfrac%20%7BF%7D%7Bx%7D)
We also know that the force F is equal to mg where m is the mass of an object and g is acceleration due to gravity hence substituting F with mg we get that
![k=\frac {mg}{x}](https://tex.z-dn.net/?f=k%3D%5Cfrac%20%7Bmg%7D%7Bx%7D)
Substituting m with 425 g which is equivalent to 0.425 kg and g with 9.81 then 0.67 for x we get that
![k=\frac {mg}{x}=\frac {0.425\times 9.81}{0.67}=6.222761194 N/m\approx 6.22\ N/m](https://tex.z-dn.net/?f=k%3D%5Cfrac%20%7Bmg%7D%7Bx%7D%3D%5Cfrac%20%7B0.425%5Ctimes%209.81%7D%7B0.67%7D%3D6.222761194%20N%2Fm%5Capprox%206.22%5C%20N%2Fm)
Therefore, the spring constant is approximately 6.22 N/m
Answer:
Explanation:
Radius of the ball is ![R=11cm=0.11m](https://tex.z-dn.net/?f=R%3D11cm%3D0.11m)
Initial speed of the ball is ![v_{com0}=6.0m/s](https://tex.z-dn.net/?f=v_%7Bcom0%7D%3D6.0m%2Fs)
Initial angular speed of the ball is ![\omega = 0](https://tex.z-dn.net/?f=%5Comega%20%3D%200)
Coefficient of kinetic friction between the ball and the lane
is ![\mu =0.35](https://tex.z-dn.net/?f=%5Cmu%20%3D0.35)
Due to the presence of frictional force, ball moves with
decreasing velocity.
(a)
velocity
in terms of
is
![V_{com0} = -R\omega\\\\=-(0.11m)\omega\\\\= (-0.11\omega)m/s](https://tex.z-dn.net/?f=V_%7Bcom0%7D%20%3D%20-R%5Comega%5C%5C%5C%5C%3D-%280.11m%29%5Comega%5C%5C%5C%5C%3D%20%28-0.11%5Comega%29m%2Fs)
(b)
Ball's linear acceleration is given by
![a=-\mu g\\\\=-(0.35) (9.8 m/s^2)\\\\= -3.43m/s^2](https://tex.z-dn.net/?f=a%3D-%5Cmu%20g%5C%5C%5C%5C%3D-%280.35%29%20%289.8%20m%2Fs%5E2%29%5C%5C%5C%5C%3D%20-3.43m%2Fs%5E2)
(c)
During sliding, ball's angular acceleration is calculated as
![\alpha=-\frac{\tau}{I}\\\\-\frac{\mu mgR}{(\frac{2}{5}mR^2)}\\\\-\frac{2}{5}\frac{\mu g}{R}\\\\-\frac{2}{5}\frac{(0.35)(9.8)}{0.11}\\\\-77.95rad/s^2](https://tex.z-dn.net/?f=%5Calpha%3D-%5Cfrac%7B%5Ctau%7D%7BI%7D%5C%5C%5C%5C-%5Cfrac%7B%5Cmu%20mgR%7D%7B%28%5Cfrac%7B2%7D%7B5%7DmR%5E2%29%7D%5C%5C%5C%5C-%5Cfrac%7B2%7D%7B5%7D%5Cfrac%7B%5Cmu%20g%7D%7BR%7D%5C%5C%5C%5C-%5Cfrac%7B2%7D%7B5%7D%5Cfrac%7B%280.35%29%289.8%29%7D%7B0.11%7D%5C%5C%5C%5C-77.95rad%2Fs%5E2)
(d)
The time for which the ball slides is calculated from the
equation of motion is
![V_{cm}= V_{cm0} + at\\\\V_{cm} = V_{cm0} + (-\mu g )t\\\\-0.11\omega=6.0m/s -(3.43m/s^2 )t\\\\-(0.11) (\alpha t) =6.0 m/s - (3.43 m/s^2)\\\\- (0.11)(-77.95 rad/s^2)t = 6.0m/s - (3.43 m/s^2 )t\\\\8.5745t + 3.43t= 6.0\\\\12.0045t = 6.0\\\\t= 0.4998s](https://tex.z-dn.net/?f=V_%7Bcm%7D%3D%20V_%7Bcm0%7D%20%2B%20at%5C%5C%5C%5CV_%7Bcm%7D%20%3D%20V_%7Bcm0%7D%20%2B%20%28-%5Cmu%20g%20%29t%5C%5C%5C%5C-0.11%5Comega%3D6.0m%2Fs%20-%283.43m%2Fs%5E2%20%29t%5C%5C%5C%5C-%280.11%29%20%28%5Calpha%20t%29%20%3D6.0%20m%2Fs%20-%20%283.43%20m%2Fs%5E2%29%5C%5C%5C%5C-%20%280.11%29%28-77.95%20rad%2Fs%5E2%29t%20%3D%206.0m%2Fs%20-%20%283.43%20m%2Fs%5E2%20%29t%5C%5C%5C%5C8.5745t%20%2B%203.43t%3D%206.0%5C%5C%5C%5C12.0045t%20%3D%206.0%5C%5C%5C%5Ct%3D%200.4998s)
(e)
Distance traveled by the ball is
![X= V_{com,0}+ \frac{1}{2}at^2\\\\= (6.0m/s)(0.4998 s)+ 0.5(-3.43m/s^2) (0.4998 s)^2\\\\=2.57m](https://tex.z-dn.net/?f=X%3D%20V_%7Bcom%2C0%7D%2B%20%5Cfrac%7B1%7D%7B2%7Dat%5E2%5C%5C%5C%5C%3D%20%286.0m%2Fs%29%280.4998%20s%29%2B%200.5%28-3.43m%2Fs%5E2%29%20%280.4998%20s%29%5E2%5C%5C%5C%5C%3D2.57m)
(for)
The speed of the ball when smooth rolling begins is
![V_{cm} = V_{com, 0}+ at\\\\=6.0 m/s +(-3.43m/s^2 )(0.4998 s)\\\\= 4.29m/s](https://tex.z-dn.net/?f=V_%7Bcm%7D%20%3D%20V_%7Bcom%2C%200%7D%2B%20at%5C%5C%5C%5C%3D6.0%20m%2Fs%20%2B%28-3.43m%2Fs%5E2%20%29%280.4998%20s%29%5C%5C%5C%5C%3D%204.29m%2Fs)
Answer:
7.35 m/s
Explanation:
Using y - y' = ut - 1/2gt², we find the time it takes the ball to fall from the 1.2 m table top and hit the floor.
y' = initial position of ball = 1.2 m, y = final position of ball = 0 m, u = initial vertical velocity of ball = 0 m/s, g = acceleration due to gravity = 9.8 m/s² and t = time taken for ball to hit the ground.
So, substituting the values of the variables into the equation, we have
y - y' = ut - 1/2gt²
0 - 1.2 m = (0 m/s)t - 1/2(9.8 m/s²)t²
- 1.2 m = 0 - (4.9 m/s²)t²
- 1.2 m = - (4.9 m/s²)t²
t² = - 1.2 m/- (4.9 m/s²)
t² = 0.245 s²
t = √(0.245 s²)
t = 0.49 s
Since d = vt where d = horizontal distance ball moves = 3.6 m, v = horizontal velocity of ball = unknown and t = time it takes ball to land = 0.49 s.
So, d = vt
v = d/t
= 3.6 m/0.49 s
= 7.35 m/s
Since the initial velocity of the ball is 7.35 m/s since the initial vertical velocity is 0 m/s.
It is shown thus V = √(u² + v²)
= √(0² + v²)
= √(0 + v²)
= √v²
= v
= 7.35 m/s